Peptide-based electrochemical sensor with nanogold enhancement for detecting rheumatoid arthritis - Lin, Ching-Yu; Nhat Nguyen, Uyen Thi; Hsieh, Han-Yun; Tahara, Hidetoshi; Chang, Yu-Sheng; Wang, Bing-Yu; Gu, Bing-Chen; Dai, Yu-Han; Wu, Chia-Che; Tsai, I-Jung; Fan, Yu-Jui (Talanta (Oxford), 2022)
Rheumatoid arthritis (RA), an autoimmune and chronic inflammatory disorder, is an incurable disease. We developed a peptide-based electrochemical sensor using electrochemical impedance spectroscopy that can be used to detect autoantibodies for RA diagnostics. We first validated that the developed peptide showed high sensitivity and could compliment the current gold standard method of an anti-cyclic citrullinated peptide antibody (anti-CCP) ELISA. The developed peptide can be modified on the nanogold surface of the working electrode of sensing chips through the method of a self-assembling monolayer. The sensing process was first optimized using a positive control cohort and a healthy control cohort. Subsequently, 10 clinically confirmed samples from RA patients and five healthy control samples were used to find the threshold value of the impedance between RA and healthy subjects. Furthermore, 10 clinically confirmed samples but with low values of anti-CCP autoantibodies were used to evaluate the sensitivity of the present method compared to the conventional method. The proposed method showed better sensitivity than the current conventional anti-CCP ELISA method. [Display omitted]